The Impact of Price and Promotion on The Consumer's Buying Behavior in The Metropolitan Region of Bandung - Edi Supriadi; Irena Larashati; Ashila Dwiyanisa; Annita Jannah; Octaviane Herawati (Majalah Bisnis & IPTEK, 2023)
The present research endeavors to examine the impact of price and promotion on the consumer's buying behavior in the metropolitan region of Bandung. The study employs path analysis to establish that consumer choices are significantly influenced by both price and promotion. The study's sample comprises 81 customers, which accounts for 7% of the total transactions that occurred in 2019. The influence of price on consumer purchase decisions is positively correlated, whereas promotion has both a direct and indirect positive impact. The present findings are consistent with prior research, emphasizing the crucial significance of price and promotion in influencing consumer behavior. The findings have led to the formulation of suggestions for enterprises that are functioning in the region of Bandung. It is recommended to perform a thorough examination of diverse pricing benchmarks in order to evaluate competitiveness and the consumer's value proposition. It is advisable to allocate resources towards efficacious promotional strategies in order to augment consumer awareness and stimulate interest in products. The implementation of successful promotional strategies has the potential to exert a favorable impact on the purchasing behavior of consumers. Additional research could delve into alternative factors that may influence consumer decision-making, thereby augmenting comprehension of consumer behavior through the inclusion of supplementary variables. The research acknowledges a number of constraints. The study exclusively centers on the influence of price and promotion in relation to purchase behavior, disregarding other variables such as product excellence, brand image, and customer support. Subsequent studies may consider incorporating these variables to conduct a more thorough analysis. Notwithstanding the aforementioned constraints, this research offers significant perspectives for enterprises in Bandung to guide their pricing and promotional approaches.